Strengthening the Role of Cadres and Village Midwives to Support the Cervical Cancer Awareness Movement in Puhu Payangan Village, Gianyar, Bali, Indonesia - Desak Putu Oki Lestari; Sri Ratna Dewi; Ni Wayan Armerinayanti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Cervical cancer is the most common type of cancer in Balinese women, and most of the cervical cancer patients came in advanced condition. The health survey conducted in the village of Puhu, Payangan, Gianyar, found that the coverage of cervical cancer screening is 12%, which is considered as low. Payangan’s sub-district health centers (Puskesmas) have made an effort to give free PAP smear screenings to the local community, but it still has not received a good response. This is related to the community’s lack of knowledge on cervical cancer, low awareness of cancer screening, and false stigma about PAP smear examination. To overcome this problem, an effort is needed to increase awareness about the need for PAP smear screening by shaping it into a cervix cancer awareness movement